Metabolic changes upon GLS inhibition by CB-839 in glioma cell lines - Santos Jiménez, Juan de los; Rosales, Tracy; Ko, Bookyung; Márquez-Gómez, Javier; Berardinis, Ralph J. de; Mates-Sánchez, José Manuel (My University, 2012)
Many tumors use Gln for both energy generation and as a biosynthetic precursor. Glutaminases (GAs) catalyze the first step of glutaminolysis by converting glutamine (Gln) into glutamate and ammonia in the mitochondria. In humans, two genes encode for glutaminases: GLS and GLS2. We examined the metabolic consequences of inhibiting GLS activity in glioma cells by using the clinically relevant inhibitor CB-839. We treated three glioblastoma (GBM) cell lines with CB-839 and performed untargeted metabolomics and isotope tracing experiments using U-13C-labeled Gln and 15N-labeled Gln in the amido group to ascertain the metabolic fates of Gln carbon and nitrogen. Untargeted metabolomics results showed that CB-839 treatment significantly depleted tricarboxylic acid cycle (TCAC) intermediates and related metabolites in the three human glioblastoma cell lines assayed. This result was also confirmed by a lower labeling from U-13C- Gln in these metabolites. U-13C- Gln tracing also revealed reductive carboxylation-related labeling in these cell lines, and this pathways was also suppressed by CB-839. Metabolomics results showed an accumulation of the de novo purine biosynthesis intermediates inosine monophosphate and/or AICAR, and a decrease in uridine monophosphate, while 15N-Gln tracing results showed a decreased labeling from Gln amido group in AMP, GMP, UMP and CTP in T98G cell line when treated with CB-839. Finally, metabolomics showed higher levels of trimethyllysine and, in T98G cells, a 22-fold increase in 5-methyl-cytosine.
Keywords: Gliomas; Cáncer; Cancer; Metabolism; Metabolomics; Glioblastoma; Glutaminase